Economic integration and agglomeration of multinational production with transfer pricing - Hayato Kato; Hirofumi Okoshi (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2019)
Do low corporate taxes always favor multinational production in the course of economic integration? We build a two-country spatial model with different corporate tax rates in which multinational enterprises (MNEs) can manipulate transfer prices in intra-firm trade. Using transfer pricing, MNEs can shift profits between domestic production plants and foreign distribution affiliates. In the initial stage of integration, more MNEs locate their production plants in the low-tax country, and then in the later stage, this location pattern reverses. Contrary to conventional wisdom, high taxes may favor multinational production, which does not yet necessarily bring greater tax revenues. The results have implications for empirical studies and tax competition between unequal-sized countries.
urn:nbn:de:bvb:19-epub-62013-2
Keywords: F12; F23; H25; H26; 330; Transfer price; Production location; Economic integration; Intra-firm trade; Economic geography